1998
DOI: 10.1002/lt.500040411
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a positive T-lymphocytotoxic crossmatch on hepatic allograft survival and rejection

Abstract: The influence of crossmatching in liver transplantation is still controversial, and at present, our unit does not alter management according to the result of standard lymphocytotoxicity testing. This study retrospectively assessed outcome of grafts transplanted in the presence of preformed antidonor cytotoxic antibody. One hundred twelve patients undergoing their first orthotopic liver transplantation had results available (mean follow-up: 18 months). Twelve patients had a positive crossmatch and 100 negative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
(29 reference statements)
2
29
1
Order By: Relevance
“…12 In brief, the recipient serum obtained immediately before LDLT was tested for cytotoxic antibody against donor T or B lymphocytes. Donor lymphocytes were isolated from peripheral blood, and 1 L of the patient's serum was added for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In brief, the recipient serum obtained immediately before LDLT was tested for cytotoxic antibody against donor T or B lymphocytes. Donor lymphocytes were isolated from peripheral blood, and 1 L of the patient's serum was added for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Takaya et al 10 showed that highly sensitized cross-match-positive grafts had a poor prognosis and function in tacrolimus-based immunosuppression. Other reports indicated the higher incidence of vanishing bile duct syndrome 11 or the severity of the acute rejection episodes 12,13 in crossmatch-positive grafts. Some similar reports have proposed adverse effects of the positive results on patient or graft survival.…”
mentioning
confidence: 99%
“…Other reports indicated a higher incidence of vanishing bile duct syndrome [12], and more severe acute rejection episodes [13,14] or acute rejection within 3 months after transplantation [15] in cases with crossmatch-positive grafts. The adverse effects of a positive crossmatch on patient and graft survival are also emphasized in other reports [4,5,16,17,18,19,20,21], but the rate of hyperacute rejection or the causal association between graft loss and acute rejection is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, effects of positive cross-match in liver transplantation remain controversial, although a number of recent studies suggested that these antibodies might increase the risk for both rejection and early graft failure in liver transplantation. [3][4][5][6][7] Recent studies have provided pathological confirmation that immunoglobulin G lymphocytotoxic antibodies could adversely affect the human liver allograft. 8 Conversely, human liver transplants classically have been reported to be resistant to antibody-mediated rejection, and transplantation has been performed successfully with positive antidonor cross-matches, established by the standard microlymphocytotoxicity test.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 More recent results from other studies contradicted these findings, showing a greater rejection rate and worse graft survival in patients who had a positive crossmatch. [3][4][5][6][7] Recently, living donor liver transplantation (LDLT) is performed increasingly because of a shortage of cadaveric donors. Adult-to-adult LDLT is limited by the need to transplant sufficient liver mass while preserving donor safety.…”
mentioning
confidence: 99%